The Catholic Church's teaching on church-state relations at Vatican II: an interpretation, critique, and suggested reform - Ciftci, M (2021)
This thesis seeks to answer three questions: What did the Catholic Church teach about church-state relations at the Second Vatican Council? What problems can we identify in that teaching? How should those problems be remedied?